EFEKTIVITAS KOMBINASI EKSTRAK JAHE DAN PIRIDOKSIN UNTUK MENGURANGI MUAL MUNTAH IBU HAMIL - Hesti Kurniasih; Fitria Zuhriyatun; Siti Nur Faizah (POLTEKKES KEMENKES SEMARANG, 2019)
The Effectiveness Of Combination Of Ginger And Pyroxoxine Extract To Reduce Pregnant Women Moment Nausea vomiting is one of the most common complaints experienced by pregnant women in the first 3 months, the condition can be a serious condition that is hyperemesis gravidarum which results in disrupting the welfare of the mother and fetus, the essential content of ginger to overcome nausea and vomiting. This study aims to assess the effectiveness of a combination of ginger extract and pyridoxine in reducing complaints of nausea and vomiting in pregnant women under 3 months. A quasi- experimental, prospective randomized controlled study method involving pregnant women with a gestational age of ≤11 weeks in the working area of Puskesmas 1 2 Baturraden. The treatment group received a combination of 200 mg of ginger extract given 3 times daily + pyridoxine 15 mg once daily for 7 days while the control group received pyridoxine 1 x 25 mg per day for 7 days. Complaints of nausea and vomiting were measured using the Rhodes Index. After 7 days of data processing, the significance value of the chi-square test p- value was 0,000 and the chi-square value of 41,060 3,841. Because the significance value of 0.000 (0.05) or the calculated chi square value of 41.060 3.841 means that there is a relationship between the treatment of ginger extract and pyridoxine turns out to be significantly more significant in reducing complaints of nausea and vomiting of pregnant women compared to pyridoxine alone.